Propuesta de un plan estratégico de marketing para el centro particular de educación básica Liceo Americano de la ciudad de Loja - Cabrera Contento, César Alberto (2015)
Through this research that had as its overall objective the "PROPOSAL FOR A STRATEGIC MARKETING FOR PARTICULAR basic school AMERICAN HIGH SCHOOL CITY OF LOJA" is to have an addressing the objectives of the institution accessing reach stability and permanence in the market and increase profitability. To meet this goal was necessary to use scientific, deductive, mathematical, statistical and documentary methods, and techniques of the interview the director and surveys applied to internal customers with a total of 17 and external customers 200 served as sources of information gathering. Further it comprising external analysis of the company which comes EFE matrix whose weighted score was 2.56 which is below the average of 2.50; plus the internal analysis of the company that gives rise to the matrix (EFI), the result is 2.29 which is also below the average of 2.50. A SWOT analysis of the company is then performed, in which the strengths and weaknesses are exposed; and the threats and opportunities, then high-impact matrix is made. This determines the strategic objectives, which were, to launch an advertising campaign costing $ 2,202.5; Create full scholarships and partial scholarships maintain, at a cost of $ 6,150.; Make a promotional plan to increase and retain customers with cost $ 467; Train teachers and administrative staff at a cost of $ 3000. The total budget for the strategic plan was $ 10,419. Among the key findings consist, that the American Lyceum has opportunities to address environmental threats, and requires establishing strategies to eliminate them. Among the most important recommendations they are, at the American Lyceum implement strategic marketing planning as a mechanism for guidance and business management which will help the timely decision making